Acute gouty arthritis as a manifestation of immune reconstitution inflammatory syndrome after initiation of antiretroviral therapy - Eyer-Silva, Walter de Araujo; Salgado, Maria Cecília da Fonseca; Pinto, Jorge Francisco da Cunha; Ferry, Fernando Raphael de Almeida; Neves-Motta, Rogério; Azevedo, Marcelo Costa Velho Mendes de; Morais-de-Sá, Carlos Alberto (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
Immune reconstitution inflammatory syndrome (IRIS) in HIV-infected subjects initiating antiretroviral therapy most commonly involves new or worsening manifestations of previously subclinical or overt infectious diseases. Reports of non-infectious IRIS are much less common but represent important diagnostic and treatment challenges. We report on a 34-year-old HIV-infected male patient with no history of gout who developed acute gouty arthritis in a single joint one month after initiating highly active antiretroviral therapy.